THREE-DIMENSIONAL MODEL OF LEFT CHAMBERS OF THE HEART BASED ON ECHOCARDIOGRAPHY DATA: AN INSTRUMENT FOR DEVELOPMENT OF TRANSCATHETER VALVES - I. Yu. Zhuravleva; R. M. Sharifulin; A. V. Bogachev-Prokofiev; D. V. Nushtaev; O. Yu. Malakhova; D. P. Demidov; A. M. Karaskov (Российский кардиологический журнал, 2017)
Aim. Comparative analysis of the acquired with EchoCG method parameters of the left chambers of the heart and of mitral valve in normal state and in restrictive type of failure with further building up three-dimensional models of these variants of the fibrous anulus geometry, and of the left atrium, left ventricle and its outgoing tract.Material and methods. The study was done using 3D transthoracal and transesophageal EchoCG on Philips iE33 (Philips Healthcare, USA) in 30 patients with unchanged mitral valve (n=15) and in ischemic mitral regurgitation (n=15). Spatial configuration of the anulus fibrosus was investigated, and mitral valve, spatial and volumetric parameters of the left atrium and left ventricle. Data was processed in SciLab 4.1.2 software and exported to CATIA 5 modelling system, where the acquired curves were combined to 2 solid thin-wall models, and after linking of the surfaces — to a hard-bodied model with required thickness of the walls.Results. All studied parameters revealed significant differences (p<0,001) in groups comparison. In restrictive type of insufficiency, sizes of fibrous anulus increase: intercomissural diameter by 22%, front-back — by 13%, perimeter — by 28%, surface — by 79%. End systolic and diastolic volumes of the LV increase more than 2 times, which is related with more prominent sphericity of the LV, than normally. Increase of LA more than 1,5 times also combines with its geometry change towards sphere. Three dimensional computer model of the left heart chambers changed as a result of ischemic mitral failure, is created. The model can be implemented in creation, analysis and prediction of medical devices for the position and/or realized as the full-sized mockups, test systems and phantoms for development and education.Conclusion. The investigation of mitral valve characteristics and of the left heart chambers by method of 3D transthoracal and transesophageal echocardiography makes it to obtain the baseline data necessary for creation of 3D computed models of the anatomic area normal and disordered. Such models can be implemented in the development of implanted devices constructions, preliminary tests of medical devices and in training.